Correlation and path coefficient analysis of grain yield with yield components of bread wheat (Triticum aestivum L.) variety Adana-99 - Noori, Shang Haseeb Abdulqader; Ghafoor, Shwana Ahmad Hussain (Sulaimani Journal for Pure and Applied Sciences, 2018)
The study performed to determine the relationship between yield and yield components of wheat (Triticum aestivum L.) variety Adana-99, using data from a factorial experiment; 6 planting dates and 6 plant densities in CRBD within three replications. Results of the path coefficient confirmed that, grain yield was positively and highly significant associated with plant height, number of days to flowering, number of days to maturity, spike length, number of spikes/m2, number of seeds/spike, 1000 grain weight, biological yield, harvest index and grain yield. Path coefficient analysis showed that the magnitude of positive direct effect on grain yield was highest through number of days to maturity which was (0.657) and followed by biological yield (ton/ha) which was (0.650), whereas number of days to flowering with (-0.425) recorded maximum negative direct effect on grain yield. The results suggest that all the characters showing highly significant correlation with grain yield in the process selection much attention should be given to them as these characters in future wheat breeding programs for increasing yield.
Keywords: Wheat; Correlation coefficient; path analysis; direct and indirect effect on grain yield